2017
DOI: 10.18203/2349-2902.isj20175405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute inflammatory score and Alvarado score in diagnosis of acute appendicitis at a tertiary care hospital

Abstract: Background: Acute appendicitis remains as one of the most common surgical entity requiring early intervention. Hence there is always a need to develop a well-designed protocol for diagnosis and to reduce negative appendectomy. The most common and widely applied was Alvarado score and best performed in validating studies, but was observed with few drawbacks. A recently introduced appendicitis inflammatory response score (AIR) was designed to overcome the drawbacks associated with the implementation of Alvarado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
2
9
0
1
Order By: Relevance
“…But in Alvarado scoring, 17 cases were in high risk and 20 cases in low risk group. 23 It was observed in the present study that for scores >4, AIR score has higher sensitivity and specificity (98.33% and 91.20%) as compared to Alvarado score (81.33% and 12.33%). The negative predictive value (NPV) of AIR score and Alvarado score was 81.66% and 78.26% respectively while the positive predictive value (PPV) of AIR score and Alvarado score was 89.22% and 54.92% respectively.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…But in Alvarado scoring, 17 cases were in high risk and 20 cases in low risk group. 23 It was observed in the present study that for scores >4, AIR score has higher sensitivity and specificity (98.33% and 91.20%) as compared to Alvarado score (81.33% and 12.33%). The negative predictive value (NPV) of AIR score and Alvarado score was 81.66% and 78.26% respectively while the positive predictive value (PPV) of AIR score and Alvarado score was 89.22% and 54.92% respectively.…”
Section: Discussionsupporting
confidence: 43%
“…In these cases, PPV turned out to be 1.00 for AIR scoring and 0.77 for Alvarado scoring. 23 Patil S et al, study reported sensitivity of AIR of 89.9% (at score >4), Both AIR and Alvarado (at score >8) demonstrated specificity of 12.3% and 21.3% respectively and specificity of Alvarado (at score >4) at 54.5%. 22 Sudhir S et al, study reported cases of phlegmonous appendicitis, for scores >4, Alvarado score has high sensitivity (97.06) compared to AIR score (78.43).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Particularly among the children, elderly and females of reproductive age, where other conditions can present with signs and symptoms similar to those of acute appendicitis, diagnosis is difficult to establish. 1,2 Management of patients with equivocal diagnosis is also controversial. 2,3 Delay in treatment increases the incidence of complications.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Management of patients with equivocal diagnosis is also controversial. 2,3 Delay in treatment increases the incidence of complications. 4,5 Diagnosis of acute appendicitis is eminently clinical, being supplemented with laboratory findings and imaging modalities.…”
Section: Introductionmentioning
confidence: 99%